Quantitative evaluation of the movement from complexity toward simplicity in the structure of thesaurus descriptors - Amirhosseini, Maziar; Salim, Juhana; Amirhosseini, Maziar; Salim, Juhana (Malaysian Journal of Library and Information Science, 2017)
Amirhosseini, M., & Salim, J. (2015). Quantitative evaluation of the movement from complexity toward simplicity in the structure of thesaurus descriptors. Malaysian Journal of Library and Information Science, Vol.20, no. 3: 47-62. The concepts of simplicity and complexity play major roles in information storage and retrieval in knowledge organizations. This paper reports an investigation of these concepts in the structure of descriptors. The main purpose of simplicity is to decrease the number of words in the construction of descriptors as this idea affects semantic relations, recall and precision. ISO 25964 has affirmed the purpose of simplicity by requiring splitting compound terms into simpler concepts. This work aims to elaborate the standard methods of evaluation by providing a more detailed evaluation of the descriptors structure and identifying effective factors in simplicity and complexity results in the structure of thesauri descriptors. The research population is taken from the descriptors of the Commonwealth Agricultural Bureaux (CAB) Thesaurus, the Persian Cultural Thesaurus (ASFA) and the Chemical Thesaurus. This research was conducted using the statistical and content analysis method. In this research we propose a new quantitative approach as well as novel indicators and indices involving Simplicity and Factoring Ratios to evaluate the descriptors structure. The results will be useful in the verification, selection and maintenance purposes in knowledge organizations and the inquiry method can be further developed in the field of ontology evaluation.